Is absolute secularity conceivable?. Issue 1 (2nd January 2017) - During, Simon
ABSTRACT: This paper critically examines the prospects for thoroughly secular thought. It does so in relation to recent theories of secularization (and especially Charles Taylor's and Hans Blumenberg's) as well as by attending to two very different intellectual projects, one mounted by Jeremy Bentham (in particular his concept of felicity or happiness), the other by Michael Oakeshott. It argues that Bentham's utilitarian account of happiness depends on a Christian conceptual structure, and that Oakeshott's understanding of philosophy as a practice of questioning presents a brighter hope for thoroughly secular thought.